Sense of generalised self-efficacy and body mass index, diet health quality and pro-health behaviours of nursing students and active professional nurses - Maria Gacek; Grażyna Kosiba; Agnieszka Wojtowicz (Nofer Institute of Occupational Medicine, 2023)
Background Personal resources are one of the determinants of lifestyle and health. The aim of the research was to analyze the relationship between sense of generalized self-efficacy, and body mass index (BMI), diet health quality and health behaviors of female nursing students and active professional nurses. The analyzed variables in the group of students and nurses were also compared. Material and Methods The study was conducted among a group of 269 women (174 students and 95 nurses working at hospitals), using: the Beliefs and Eating Habits Questionnaire (KomPAN), Juczyński's Health Behavior Inventory (HBI) and the Generalized Self-Efficacy Scale (GSES). The BMI was assessed on the basis of anthropometric measurements. Statistical calculations were performed using analysis of variance, the Student's t-test, multivariable regression analysis and Pearson's correlation as well as moderation analysis, with the adopted level of statistical significance at α = 0.05. Results Professionally active nurses achieved higher BMI levels (25.95 vs. 22.31 kg/m 2 , p 0.05). Conclusions Nurses with a higher sense of self-efficacy declared a higher diet health quality and healthier behaviors, and their BMI was related to diet quality and health behaviors. Med Pr Work Health Saf. 2023;74(4):251-61.